A newly designed benzodithiophene building block: tuning of the torsional barrier for non-halogenated and non-aromatic solvent-processible photovoltaic polymers. Issue 13 (14th March 2023) - Cho, Hye Won; Jeong, Sang Young; Wu, Ziang; Lim, Hyojin; Park, Won-Woo; Lee, Woojin; Suman Krishna, Jonnadula Venkata; Kwon, Oh-Hoon; Kim, Jin Young; Woo, Han Young
Abstract : A new benzodithiophene (BDT)-based building block, 3-FBDT, was synthesized and incorporated into PBDB-T-2F to yield an eco-friendly (non-aromatic and non-halogenated) solvent-processible photovoltaic copolymer, PBDB-T-2F(3/4). Abstract : A new benzodithiophene (BDT) building block, 4, 8-bis(5-(2-ethylhexyl)-3-fluoro-4-hexylthiophen-2-yl)benzo[1, 2- b :4, 5- b ′]dithiophene (3-FBDT), was designed by tailoring the positions and number of alkyl and F substituents by adjusting the torsional energy barrier. The incorporation of 3-FBDT into a representative BDT-based polymer donor (PBDB-T-2F) yielded a new photovoltaic copolymer (PBDB-T-2F(3/4)) with a decreased valence band level and considerably improved solubility in non-halogenated and non-aromatic solvents such as tetrahydrofuran (THF). Side-chain engineering has been widely studied to control solution processability in eco-friendly solvents, but the torsional property control of conjugated main chains has rarely been attempted. Although PBDB-T-2F showed a significant drop in power conversion efficiencies (PCEs: 17.46 to 9.73%) owing to serious aggregation caused by replacing chloroform with THF as a processing solvent, the THF-processed PBDB-T-2F(3/4) device maintained a high PCE (14.3 to 13.86%) with little detrimental effect. Charge carrier dynamics and film morphology analyses suggested that the electronic and morphological properties of PBDB-T-2F(3/4) are mainly governed by the majority moiety of the PBDB-T-2F blocks. Owing to its high solubility and outstanding photoelectrical properties, PBDB-T-2F(3/4) was successfully employed to fabricate flexible, semi-transparent, and large-area THF-processed devices. The incorporation of the 3-FBDT building block into various BDT-based photovoltaic polymers can be an effective strategy to improve the solution processability and broaden the solvent selection for fabricating eco-friendly solar cells without significantly disrupting their photoelectrical properties.